Root coverage of a previously restored tooth. A case report with a 7-year follow-up - Alexander Corsair (Dove Medical Press, 2009)
Alexander CorsairPrivate Practice, RockvilleCentre, NY, USAAbstract: This case report describes the treatment of a maxillary canine that had 4 mm of marginal gingival recession. The exposed root had been previously restored with a composite class 5 restoration. The restoration was removed and the root planed and demineralized. The root was then covered by a subepithelial connective tissue graft harvested from the palate. The flap was coronally positioned to completely cover the graft and exposed root. The healing was photographed post-operatively at one month, six months, and seven years. Root coverage increased to 100% after seven years. The zone of attached gingiva also increased.Keywords: coronally positioned, subepithelial, connective tissue graft, keritinized gingiva, creeping reattachment